Identifikasi Jenis Ikan Demersal di Pasar Tanjung Luar, Lombok Timur - Rusmawati, Ika; Ningrum, Audya Septria; Rosiyani, Amita Dwi; Sasmitha, Yuan; Dewi, Saskia Septina; Riandinata, Selamet Kurniawan (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2023)
The Tanjung Luar fish market is a place to find catches as well as a place to market them. There are various fish species including demersal fish species at the Tanjung Luar Fish Market, East Lombok District. The research was conducted in October 2022 with research method used is a survey and documentation method. Based on the results of the study, 25 species of demersal fish were found that belong to 12 families, namely Acanthurus lineatus, Heniochus singularius, Platax boersii, Plectorhinchus polytaenia, Plectorhinchus vittatus, Diagramma pictum, Choerodon anchorago, Cheilinus chlorourus, Paracaesio xanthura, Lutjanus fulvus Parupeneus multifasciatus, Pentapodus bifasciatus, Pseudorhombus sp., Chlorurus bleekeri, Cephalopholis argus, Cephalopholis cyanostigma, Cephalopholis urodeta, Epinephelus areolatus, Epinephelus hexagonatus, Epinephelus coioides, Epinephelus merra, Plectropomus maculatus, Siganus sp., Siganus gutattus, and Siganus canaliculatus. The most common demersal fish species found in Tanjung Luar Fish Market is Ikan Janggut (Parupeneus multifasciatus).